THE INFLUENCE OF EMPLOYEES TRAINING AND ACCOUNTABILITY ON SERVICE DELIVERY IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Employee training refers to the skill equipping functions that many employers now offer to their employees. These are the functions that Human Resources staff perform relative to the organization’s employees and include recruiting, hiring, compensation and historically, the exact origin of Accountability is not clear. However Mulgan, (2009) noted that the advent of Accountability can be traced right from the Industrial Revolution that took place in Britain. During the early part of the Industrial Revolution, many of the early firms went bankrupt. Little credit went to manufacturing operations and continuing operations and expansion was funded primarily from retained earnings (Morduch. 2009). Thus, during depressionsbenefits